(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The global expansion of sales services has become a critical aspect of business success, especially for emerging economies like Uzbekistan, which is positioning itself as a significant player in the global market. With increasing globalization and the rapid digitalization of industries, Uzbekistan’s trade and service sectors are evolving rapidly to meet international standards. This article explores the strategies, innovations, and advantages associated with the global development of sales services in Uzbekistan. It analyzes the unique opportunities and challenges faced by Uzbek businesses as they expand their sales operations internationally. Furthermore, it discusses how technological innovations, customer-centric approaches, and government policies play pivotal roles in shaping the global sales services landscape in the country. The article concludes with strategic recommendations for businesses seeking to capitalize on global market opportunities while enhancing their sales service models.